A responsabilidade civil e penal do médico em face dos Institutos da Eutanásia, Ortotanásia e da Distanásia. - PEGORARO, Geizy Hellen (2020)
Over the past few decades, medical technology has significantly advanced. Consequently, new methods, capable of artificially extending the life of a human being, or even shortening it, have emerged. Thereby, the main focus of the present work is to analyze the legal aspects, starting from medical situations related to interventions at the end of human life, either to interrupt the life of a patient or to prevent it from ending, as well as the civil and criminal liability of medical professionals who perform such conduct, since it’s the professional’s responsibility to adopt the necessary measure so that their patient has a dignified and painless death. Thereby the theme will be examined based on the principle of human dignity, as well as it will be analyzed if such institutes violate the constitutional principles and the current Brazilian laws. The present work is extremely important, as it deals with practices that are common in hospitals in Brazil, however they are rarely discussed, given that it is a controversial subject that generates dissension. For this reason, the research theme is considered relevant, since it contributes to the advancement of law and this must accompany the changes in society and, consequently, the conflicts that arise with technological innovations in the field of medicine. Therefore, for the analysis of the theme, the deductive research approach was used, based on bibliographic research, which consists of consulting books and scientific articles.